2020
DOI: 10.1002/adom.202000359
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Controllable Terahertz Second‐Harmonic Generation in GaAs

Abstract: Terahertz radiation and its nonlinear optical manipulation may possess potential for a variety of applications in next‐generation electronics and optics. Pioneering studies have shown that the nonlinearity of carrier drift in semiconductors and graphene can be utilized for nonlinear optical processes at terahertz frequencies. However, because of the symmetric response of carriers to the terahertz field direction, most experiments have confirmed only the presence of odd‐order nonlinear processes. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…This is the first report of such χ (2) tuning and reversibility in nonlinear thin films. This positions our PZT thin films as an ideal candidate for new functionalities in thin films and integrated optics such as on‐chip optical parametric oscillators, frequency comb generators, [ 44 ] terahertz sources, [ 45 ] quantum sources, [ 46 ] and frequency converters. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of such χ (2) tuning and reversibility in nonlinear thin films. This positions our PZT thin films as an ideal candidate for new functionalities in thin films and integrated optics such as on‐chip optical parametric oscillators, frequency comb generators, [ 44 ] terahertz sources, [ 45 ] quantum sources, [ 46 ] and frequency converters. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…e) Reproduced with permission. [293] Copyright 2020, Wiley-VCH. related to the THz field oscillations because the electro-optic properties of GaP show an instantaneous modification.…”
Section: Nonlinear Phase Modulationmentioning
confidence: 99%
“…Recently, a study demonstrated electric field-induced second-harmonic generation (EFISHG) in the THz frequency in photoexcited GaAs by exploiting the highly nonlinear properties of electron drift transport and breaking its directional symmetry with an additional bias field. [293] The second-harmonic www.advopticalmat.de Adv. Optical Mater.…”
Section: Thz Reemission and Harmonic Generationmentioning
confidence: 99%
“…Alternatively, applying a DC bias field to a third-order nonlinear material can also induce a second-order nonlinear susceptibility, enabling electric-field-induced SHG (EFISHG). Electrically tunable dielectric metasurfaces for enhanced and controlled nonlinear optical emission have been recently studied theoretically 211 and also experimentally in bulk GaAs 212 and Si metasurfaces. 213 Research in high-harmonic generation and wave mixing phenomena started to develop only less than 5 years ago and have the added experimental complexity of multiple beam excitation or extended working spectral ranges.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…Alternatively, applying a DC bias field to a third-order nonlinear material can also induce a second-order nonlinear susceptibility, enabling electric-field-induced SHG (EFISHG). Electrically tunable dielectric metasurfaces for enhanced and controlled nonlinear optical emission have been recently studied theoretically and also experimentally in bulk GaAs and Si metasurfaces …”
Section: Conclusion and Perspectivesmentioning
confidence: 99%